Hierarchical QoS admission control mechanism for IEEE 802.16j mobile multihop relay WiMAX network / Rohaiza Yusoff - Yusoff, Rohaiza (2014)
With the advancement in telecommunication technology, Mobile Multi-hop Relay (MMR) Worldwide Interoperability for Microwave Access (WiMAX) network was introduced to meet the increase in user demand. Scheduling is one of the most crucial factors which influenced the quality of service(QoS) in WiMAX network. This research is focused on the admission control coupled with Round Robin scheduler to avoid overwhelming the limited radio resources due to many connections. The simulation study was done using Network Simulator version 2 (NS2) attached with National Chiao Tung University network simulator (NCTUns) module package with hierarchical QoS priority mechanism. The results show that the proposed admission control mechanism is able to decrease the radio resources wastage about 35%.Different mobile station densities were deployed to observe on the system capability. The knowledge on the handover behaviour for WiMAX network is essential in network management and planning in order to achieve optimum system throughput. In this research the analysis of handover behaviour is performed for several transparent relay configurations in IEEE 802.16j MMR WiMAX network. The simulation was performed using NCTUns tools and adopted the hard handover mechanism for three different relay network topologies with varying mobile station speeds. The results show the handover for intra network is faster than the inter network, by selecting appropriate relay deployment the system throughput can be increased up to 14.39%.